Review of intraluminal optical coherence tomography imaging for cerebral aneurysms - Ku, Jerry C.; Pasarikovski, Christopher R.; Dobashi, Yuta; Ramjist, Joel; Priola, Stefano M.; Yang, Victor X. D. (Frontiers in Photonics, 2022)
Cerebral aneurysms are an abnormal ballooning of blood vessels which have the potential to rupture and cause hemorrhagic stroke. The diagnosis, treatment, and monitoring of cerebral aneurysms is highly dependant on high resolution imaging. As an imaging modality capable of cross-sectional resolution down to 10 micrometers, intraluminal optical coherence tomography (OCT) has great potential in improving care for cerebral aneurysms. The ability to assess the blood vessel microanatomy in vivo may be able to predict aneurysm growth and rupture. During treatment, intraluminal OCT may aid in assessment of treatment efficacy and complication avoidance, such as via visualization of in-stent thrombosis, stent wall apposition, and the fate of covered branch vessels. This technology can also be used in post-treatment monitoring, to assess for aneurysmal remnants or for endothelialisation and healing over the diseased segments. The goal of this clinically focused narrative review is to provide an overview of the previous applications of intraluminal OCT in cerebral aneurysms and future prospects of applying this technology to improve care in patients with cerebral aneurysms, including a specific neurovascular OCT catheter, doppler OCT for high resolution blood flow assessment, and further research endeavors.